What Can We Do to Improve the Contribution of European Grassland to Net Food Security? - Hennessy, Deirdre; Rinne, Marketta; Eriksen, Jørgen; Delaby, Luc (Wiley-Blackwell, 2025)
Intensification of animal production systems over the last number of decades has increased the consumption of human edible protein by livestock, leading to increased competition for and cost of human edible protein. Grassland-based agriculture supports ruminant production systems, which convert human inedible proteins (grassland) into human edible meat and dairy products with high nutrient density. Grassland-based systems have a low reliance on human edible food for production, and therefore optimizing the use of grassland to produce animal protein contributes to food security. Grassland-based systems have conversion efficiencies of 2.5 to 4 in terms of kg human edible protein produced for each 1 kg human edible protein consumed by livestock, greater than that of confinement systems (≤ 1 for each 1 kg human edible protein consumed). Managed grassland offers a range of other ecosystem services including supporting plant and animal biodiversity, water resource management (e.g., water retention, provision of flood plains, water filtration), carbon storage and sequestration, and cultural services. Grassland management, sward species selection, and supplementation are amongst the strategies that can be used to optimise grassland production and utilisation by ruminants for human edible-food production to contribute to global net food security, as well as environmental conservation and management.
Keywords: food security; food-feed competition; grasslands; ruminant production